Tax Fraud in Financial Statement – Identifying and Measuring Tax Evasion Factors (A Literature and Methodological Review) - Kodra, Blerta; Dhamo, Sotiraq (44th International Conference on Organizational Science Development: Human Being, Artificial Intelligence and Organization, Conference Proceedings, 2025)
The purpose of this article is to present the first part of the doctoral thesis “Tax Fraud in Financial Statement in Albania”, where tax fraud is considerate as a form of tax evasion done with purpose. To the best of our knowledge there is no study who summaries the tax evasion determinants and the methodological used to identify and measure these variables. Specifically, this study adopted a systematic review of 53 articles published in the past 15 years, summarising the methodologies used for identifying and measuring tax evasion determinants. Our findings show that many studies have measure economic and individual factors and there is less study focused on technology, competition between businesses, business expansion, corporate social services and failure to not receive reimbursement from the government. Additionally, it looks like there is no widely accepted method for measuring tax evasion factors. This research paper contributes in tax literature by regrouping the tax evasion factors in new categories.